“Communal News Work” as Sustainable Business Model: Recent Print-Centric News Start-Ups in Regional Queensland - Harry Dugmore; Renee Barnes; Peter English; Elizabeth J. Stephens; Rosanna Natoli (Media and Communication, 2024)
The Covid-19 emergency in Australia precipitated the closure of dozens of print newspapers across Australia but, conversely, the heightened state of anxiety of the early Covid-19 period amplified the need for local information and communality. This was the impetus for a wave of print-centric newspaper start-ups. We previously examined 22 Covid-19 era start-ups in Queensland (see Barnes et al., 2022, p. 21–34) and found that their editors/publishers universally “reassert(ed) and claim(ed) more vigorously the normative values associated with community journalism as ‘social glue.’” These proprietors deployed an “affective rationale” as the foundation of their journalism and their “lean start-up” business models. We called this a “community cohesion model.” Returning to these start-ups 18 months after the Covid-19 pandemic restrictions were lifted in Queensland, we find that about 60% of these newspapers have continued operating, still drawing on deep wells of community support. They are transitioning to more conventional “newsonomics,” seeking—like the news organisations they replaced—to expand their advertising and raise other revenue, keep costs low, and expand their digital channels while remaining focussed on their core print offering. Drawing on in-depth interviews and editorial statements by editors/owners of these start-ups, as well as a close examination of advertising in the surviving newspapers, this study argues that adopting affective “hybrid” business models can be a basis for news organisations’ longer-term viability.